Medical Imaging 2018: Biomedical Applications in Molecular, Structural, and Functional Imaging 2018
DOI: 10.1117/12.2294558
|View full text |Cite
|
Sign up to set email alerts
|

Toward modeling the effects of regional material properties on the wall stress distribution of abdominal aortic aneurysms

Abstract: The overall geometry and different biomechanical parameters of an abdominal aortic aneurysm (AAA), contribute to its severity and risk of rupture, therefore they could be used to track its progression. Previous and ongoing research efforts have resorted to using uniform material properties to model the behavior of AAA. However, it has been recently illustrated that different regions of the AAA wall exhibit different behavior due to the effect of the biological activities in the metalloproteinase matrix that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Contrast enhanced computed tomography angiography (CTA) images of 66 patients were retrospectively obtained from the Division of Vascular Surgery at the University of Rochester following approval by the Human Subject Review Board. The images were used to calculate 26 geometrical indices and 4 biomechanical parameters, details of which are available in [11,20,21]. Moreover, 15 patient-specific clinical factors, consisting of patient demographics, habitual information such as risk factors, and other clinical pre-existing conditions, were also extracted from the clinical dataset.…”
Section: Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrast enhanced computed tomography angiography (CTA) images of 66 patients were retrospectively obtained from the Division of Vascular Surgery at the University of Rochester following approval by the Human Subject Review Board. The images were used to calculate 26 geometrical indices and 4 biomechanical parameters, details of which are available in [11,20,21]. Moreover, 15 patient-specific clinical factors, consisting of patient demographics, habitual information such as risk factors, and other clinical pre-existing conditions, were also extracted from the clinical dataset.…”
Section: Datasetsmentioning
confidence: 99%
“…Moreover, it has been shown that in addition to geometric indices such as D max , a variety of biomechanical parameters and material properties affect AAA morphology and behavior [3,[7][8][9]. Wall stress distribution and mainly the peak wall stress -which is directly related to the failure site on the AAA surface -computed using finite element analysis (FEA) have been helpful to comprehensively consider the effects of all mentioned parameters [10][11][12]. Additionally, it has been illustrated that patient-specific historical data, such as the presence of clinical pre-existing conditions or risk factors, such as smoking, hypertension, or chronic kidney disease (CKD) may increase AAA severity and risk of rupture [6,13].…”
Section: Introductionmentioning
confidence: 99%